MiR-205-5P AS POTENTIAL BIOMARKER AND THERAPEUTIC TARGET IN HEAD AND NECK SQUAMOUS CELL CARCINOMA - Babu, S.; Krishnan, M.; Chinnaiyan, M.; Daniel, P.; Solomon, A. (PH Akademperiodyka, 2023)
Dear Editor, Head and neck squamous cell carcinoma (HNSCC) is the 6th most common type of cancer in the world, affecting the nasal cavity, oral cavity, tongue, pharynx (nasopharynx, oropharynx and hypopharynx), and also larynx. HNSCC is estimated to affect over 500,000 people worldwide each year. Tobacco, alcohol, and human papillomavirus infection are among the risk factors for HNSCC. The primary treatment options include surgery, radiotherapy and chemotherapy. Despite current therapeutic advances, recurrence and metastatic spread remain the two primary causes of poor survival rates in patients diagnosed with HNSCC. As a result, there is an immediate requirement to find new biomarkers linked to HNSCC and to test the efficacy of therapeutic strategies in HNSCC patients [1, 2]. A biomarker is described as a single moiety or a complex mixture of biological molecules that are measured and evaluated objectively as an index of normal cellular, pathogenic, or pharmacologic reaction to a therapeutic treatment. Biomarkers could provide important insights into tumor growth and contribute to the formation of new therapies. The investigation of cancer biomarkers that can provide diagnostic, prognostic, or therapeutic info has become a needed but difficult task in cancer research [3]. The finding of miRNAs has recently piqued researchers’ interest, following the detection of Lin-4, the first member of the miRNA family, in C. elegans in 1993. An enormous number of miRNAs have been discovered and studied and a plethora of miRNAs has been recognized to revolve in human carcinogenesis by acting as “oncomiRNAs” or “tumor suppressive miRNAs”. Surprisingly, miRNAs have demonstrated excellent promise as a new group of biomarkers in cancer owing to the widespread cancer-associated abnormal expression pattern of dysregulated miRNAs as well as miRNA properties such as spatial or temporal specificity, stability and sensitivity in both paraffin specimens and body fluids [4]. MiRNAs are highly conserved non-coding RNAs of 19–24 nucleotides in length that can regulate the expression of genes by binding to the 30 untranslated regions of target messenger RNAs. Many miRNAs have already been linked to the development of cancer-related characteristics. Because of their widespread expression and ability to tightly govern the gene expression of a wide range of genes and pathways in a single hit, miRNAs are valuable therapeutic targets to pursue in the hunting for new treatment options. The miRNA system can be used for therapeutic purposes by replacing tumor-suppressing miRNAs lost in cancer or by inhibiting oncogenic miRNAs overexpressed in cancer (Figure) [5]. The information retrieved from miRNAs signatures as potential biomarkers is already providing evidence allowing us to understand better and treat discrete tumors; and the implementations of these mighty molecules in cancer therapeutics carry great promise for the future.